Everyday activity strategies perceived by people with advanced cancer: a qualitative explorative study - Karen la Cour; Lisa Gregersen Oestergaard; Marc Sampedro Pilegaard (BMC Palliative Care)
Abstract Background Despite growing research on the daily life of people with advanced cancer, more specific knowledge is needed about the specific strategies these people use to manage everyday activities. Purpose This study explores how people with advanced cancer manage their everyday activities and describe their specific strategies. Methods The qualitative study was designed with an explorative approach. Data from 28 people with advanced cancer was drawn from a trial including qualitative interviews to elicit participants’ perceptions about managing their everyday activities. Interviews were conducted in participants’ homes and analysed using an inductive thematic analysis. Results Within an overarching theme of keeping ‘Daily life as usual’, the findings unfold participants’ specific strategies identified within two sub-themes ‘, Upholding routines’ and ‘Activity adaptations’. Upholding routines related to 1) Personal care and household and 2) Leisure-, social- and work-life. Activity adaptation about 1) Working with and around physical limitations; 2) Sharing, delegating, and letting go; and 3) Enlisting ‘outside’ support. Conclusion This study specified participants’ specific and distinct self-developed strategies within routines and activity adaptations. The strategies reflect participants’ needs for maintaining functioning while relieving pain and mourning, which holds essential potential for informing person-centred intervention development integrating rehabilitation in palliative care.